Treatment of malignant ventricular arrhythmia guided by electrophysiologic study. - Brandão, L; Carpinteiro, L; Sousa, J; Vagueiro, M C (Acta Médica Portuguesa, 1998)
The purpose of this study was to assess the results of the treatment of malignant ventricular tachyarrhythmias guided by electrophysiologic studies. Thirty patients with ventricular arrhythmias, aged 56.6 +/- 14.1 years, were submitted to EP testing. The clinical presentation of arrhythmia was sustained monomorphic ventricular tachycardia in 24 (80%), non-sustained ventricular tachycardia in three and another three were survivors of sudden cardiac death. Twenty five patients (83%) had evidence of structural heart disease and left ventricular ejection fraction was less than 40% in 16 (53%). Antiarrhythmic drugs were considered effective when sustained monomorphic ventricular tachycardia was noninducible or significantly slowed in serial EP testing. Sustained monomorphic VT was induced in 19 patients (63%) and an effective drug therapy was found in 13 (68%). In the other 11 patients sustained arrhythmias were not induced, although in six of them the study was done already under antiarrhythmic drugs, that were continued in the follow-up. In the six patients in which an effective drug regimen could not be found and in two sudden death survivors with primary ventricular fibrillation and negative EP testing, an Implantable Cardioverter-Defibrillator was implanted. After 17.8 +/- 10.5 months, there was recurrence of the arrhythmia in 4 (18%) of the 22 patients on antiarrhythmic drugs and half of the patients with ICDs received appropriate therapy from the device. Three patients (10%) died in the follow-up, of which only one due to sudden death. We conclude that selection of optimal antiarrhythmic treatment based on the results of EP testing, is associated with decreased episode recurrence and sudden death.